Penggunaan Filtrasi Sebagai Teknologi dalam Pengolahan Limbah Tahu di Desa Sepande Sidoarjo - Furqonati, Lili; Fadilah, Fitrian Nur; Fitria Ayu Prayekti, Rahmatika; Kartika Putri, Aprilia; Rohmah, Jamilatur (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
There are more tofu industries in Indonesia, which means there is more waste from these sectors that need specific handling. If tofu waste with a high organic matter concentration is disposed of untreated, it might have detrimental effects on the water supply. The purpose of this study was to investigate efficient techniques for using filtration media to treat tofu waste. Combining bioball and bioring media is the primary media layout in the filtration column. The tofu industry in Sepande Village, Candi District, Sidoarjo Regency, provided the tofu waste. Each column's filtration medium has a total height of 20 cm and a 1.5-liter wastewater capacity. The results showed an improvement in the quality of tofu wastewater after treatment. Filtration media using bioballs and bioring proved effective by looking at the results of waste treatment after filtration in the form of increased pH, decreased aggressive CO2, reduced turbidity, and decreased BOD. Keywords: Tofu waste, filtrasi, bioball, bioring